Pengaruh Penerapaan Green Accounting Terhadap Kinerja Keuangan Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Radiatushalihah, Radiatushalihah; Handajani, Lilik; Astuti, Widia (CV. Rayyan Dwi Bharata, 2024)
This study aims to examine the effect of environmental performance and examine the effect of environmental disclosure on financial performance listed on the Indonesia Stock Exchange in 2018-2022. This study uses control variables, namely company size and company age. This research method uses quantitative associative. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2022 totaling 42 companies. The sampling technique in this study used purposive sampling so that 14 companies were sampled. The data is processed using panel data regression analysis. The results of the study are environmental disclosure variables affect financial performance (ROA), environmental disclosure affects financial performance (ROE), company size affects financial performance (Tobins'q) and company age affects financial performance (ROA).